2017
DOI: 10.22605/rrh4149
|View full text |Cite
|
Sign up to set email alerts
|

Retention of qualified healthcare workers in rural Senegal: lessons learned from a qualitative study

Abstract: A B S T R A C TIntroduction: Deployment and retention of a sufficient number of skilled and motivated human resources for health (HRH) at the right place and at the right time are critical to ensure people's right to access a universal quality of health care. Vision Tokyo 2010 Network, an international network of HRH managers at the ministry of health (MoH) level in nine Francophone African countries, identified maldistribution of a limited number of healthcare personnel and their retention in rural areas as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…Thus, further investigation is warranted. In addition, the qualitative study undertaken prior to the choice experiment indicated the importance of fair, transparent administration of salary and/or allowance payments [14], which also suggests that the study results on payment of allowances must be carefully interpreted and further investigation of various aspects associated with payment is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, further investigation is warranted. In addition, the qualitative study undertaken prior to the choice experiment indicated the importance of fair, transparent administration of salary and/or allowance payments [14], which also suggests that the study results on payment of allowances must be carefully interpreted and further investigation of various aspects associated with payment is required.…”
Section: Discussionmentioning
confidence: 99%
“…These groups may have different job preferences for work in rural posts than those interviewed in our study. Although this may limit the generalizability of the study results to all healthcare professionals in Senegal, a qualitative study undertaken prior to the CE, which included interviews with those currently working in Dakar who had previously worked in ‘difficult’ regions, did not find differences in factors affecting job retention in ‘difficult’ regions between those in Dakar with experience in ‘difficult’ regions and those currently working in ‘difficult’ regions [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have noted security of tenure to be an important factor informing migration decisions. In Senegal, recruitment and retention were both improved for health care workers given a permanent contract, even if the workplace was in a rural area . Another study in Lebanon found that attrition rates were significantly decreased when employees had the job security of a full‐time contract …”
Section: Discussionmentioning
confidence: 99%
“…These ndings concur with others conducted in rural Senegal and Niger. [31,32] This motivation, in our context, stems from the labour market features which is characterized by a chronic oversupply and underemployment of HCWs alongside di cult learning possibilities in urban health facilities -as a consequence of high sta ng levels of healthcare facilitiesespecially in the capital Conakry.…”
Section: Analysis Of the Post-ebola Retention Policymentioning
confidence: 99%